A Review of Personality Type D on Cardiovascular Disease Patients - Gratsia Viktoria Fernandez; Rahmatul Fitriyah; Wahyu Sukma Samudera; Hidayat Arifin; Shenda Maulina Wulandari (Universitas Airlangga, 2019)
Introduction: The type of personality that a patient has as a psychosocial factor has been associated with the incidence and progression of cardiovascular disease. The aim of the study was to review the evidence and correlation between personality type and the development of cardiovascular disease.Methods: Articles were searched for using the PRISMA approach in the CINAHL, Science Direct and Scopus databases, limited to the last 5 years. The articles were from 2013 to 2018 and the language used was English. The studies focused on personality type D and cardiovascular disease, and the participants were above 18 years old.Results: Most of the findings of the studies showed that individuals with a type D personality have a relationship with more severe heart disease, which relates to several physiological factors, namely emotion increase, anxiety, stress, biological factors, cognitive decline and the decrease in quality of life.Conclusion: Individuals with type D personality have a higher level of stress, significant blood pressure, higher pulse and they experience an increase in cortisol compared to non-type D personalities. Individuals who suffer from cardiovascular disease with personality type D tend to experience a more severe progression of the condition of cardiovascular disease.